PEMBELAJARAN MELUKIS PADAANAK MELALUI BAHASA RUPA - ., Suardana (Jurnal Cakrawala Pendidikan, 2005)
This study aims to develop the knowledge of aspect Language for the children, with expectation children could be able to create or express and have creative imagination in fine art. A child represents the new generation who later they will .. be adult and represent the expectation ofthe family and oftheir Country. In educating the nation, in broader sin~ children require full attention, not only fulfilling the need oftheir food and cloths but also need education in accordance withthere ages. Education for children should be in accordance with their needs and capacity. Children world are identical with the play or leisure that is a sensation that is full ofspontaneity and pleasure the children also like to imitate because one of their behavior forming process is imitating what happened in their surrounding environment. Basically Children have big curiosities. They wish to try, to feel, wish to fmd some thing, and so on for that reason people around them conduct or participate in the construction ofpositive growth oftheir physic and soul. One factor In develop ment ofchildren creativities in painting is through the education of aspect Language, children will easily know something through the visualization of a real thing although same times they experience inferences offamily or ofschool activities LimitingChild tendency inexpression or creation. Canhinderthe growth ofchildren creativities and initiative process. Study ofaspect language should motivation the children so that they can develop their potency. Principally, study ofaspect language is development Individual potencies. Educator ought to squire or help them with certain motivation for their expression need their develop ment for better abilities and capabilities Key words: study, paint, child, and aspect language.